EFEKTIVITAS PENYAMPAIAN STRATEGI DAN KEBIJAKAN MSDM MELALUI MEDIA KOMUNIKASI PROFESIONAL: ANALISIS DAMPAK PADA IMPLEMENTASI DI LINGKUNGAN ORGANISASI PRAKTIS - Dian Nurul Izza; Jhon Very (Jurnal Riset Multidisiplin Edukasi, 2025)
This research aims to analyze the effectiveness of Human Resource Management (HRM) strategy and policy delivery through professional communication media in practical organizational environments. Digital transformation and increasingly complex business dynamics require HRM practitioners not only to develop comprehensive analyses and policies but also to possess effective professional communication skills to ensure optimal implementation. The study employs a mixed-methods approach with sequential explanatory design, involving 135 HRM practitioners from various industrial sectors and 18 key informants through in-depth interviews. Results reveal that integrating professional communication media enhances HRM strategy implementation effectiveness by 63.8%, with interactive visual presentations (82.4%) and curated digital collaboration platforms (76.9%) being the most effective media. However, significant barriers exist, including strategic communication competency gaps (71.3%), misalignment between media format and audience characteristics (64.7%), and organizational culture resistance to communication pattern changes (59.2%). Multiple regression analysis identifies analytical-communication competency (β=0.427; p<0.01), stakeholder engagement (β=0.389; p<0.01), and contextual media adaptation (β=0.356; p<0.05) as primary success predictors. This research contributes theoretically through the development of the Strategic HR Communication Effectiveness Framework (SHRCEF) and provides practical implications via a phased implementation guide to enhance HRM practitioners' professional communication capacity in real organizational environments.